The Effects of Different Probiotic Administration on Dexamethasone-Associated Metabolic Effects - Andreea Ioana Inceu; Maria Adriana Neag; Corina Ioana Bocsan; Anca Elena Craciun; Carmen Stanca Melincovici; Dana Maria Muntean; Florentina Claudia Militaru; Mădălin Mihai Onofrei; Raluca Maria Pop; Luciana-Mădălina Gherman; Marius Bichescu; Anca Dana Buzoianu (Microorganisms)
Glucocorticoids are steroid hormones used in clinical practice as an effective therapeutic option for their effects regarding the dysregulated immune reactions and hyperactive immune system. Their administration in the short- and long-term exposure has been associated with numerous metabolic side effects. Probiotics have been shown to modulate basal metabolism, inflammation, and oxidative stress through the regulation of composition and function of the gut microbial environment. The aim of this study was to assess the effects of Saccharomyces boulardii and Lactobacillus paracasei probiotics in dexamethasone-treated rats. The study comprised four groups, with 6 Charles River Wistar albino male rats/group; group 1 represented the negative control, rats from group 2 were administered dexamethasone, rats from group 3 were administered dexamethasone and probiotics containing the strain Saccharomyces boulardii, and rats from group 4 were administered dexamethasone and probiotics containing the strain Lactobacillus paracasei. We have assessed the plasmatic levels of glucose, total cholesterol, triglycerides, tumor necrosis factor-alpha, interleukin-10, catalase activity, and total antioxidant capacity. The administration of dexamethasone led to elevated serum concentrations of glycolipid metabolism parameters and cytokines and resulted in hepatic steatosis at the morphological level. Administration of probiotics containing Saccharomyces boulardii or Lactobacillus paracasei reduced glucose and tumor necrosis factor-alpha serum concentration in dexamethasone-treated rats. Moreover, the administration of Lactobacillus paracasei probiotics in rats that received dexamethasone increased interleukin-10 and reduced catalase activity. Regarding the liver tissue morphology, the rats that received probiotics showed improved liver histological aspects compared to the dexamethasone-treated group, suggesting that probiotics could provide positive effects regarding the metabolic and histological disturbances induced by glucocorticoids.